2021
DOI: 10.3390/robotics10040123
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Conceptual Mechanical Design and Control of a New Human Upper Limb Exoskeleton

Abstract: Safe operation, energy efficiency, versatility and kinematic compatibility are the most important aspects in the design of rehabilitation exoskeletons. This paper focuses on the conceptual bio-inspired mechanical design and equilibrium point control (EP) of a new human upper limb exoskeleton. Considering the upper limb as a multi-muscle redundant system, a similar over-actuated but cable-driven mechatronic system is developed to imitate upper limb motor functions. Additional torque adjusting systems at the joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…• Zakaryan et al [58] used a weight-sum-based DE [59] to retrieve the optimal link and joint weights that minimize (i) the total mass of the device, (ii) the maximal magnitudes of cable tensions, and (iii) the maximal difference between magnitudes of agonist-antagonist cable tensions (i.e., to resemble the structure of the natural muscular system of human limbs) of their arm exoskeleton for rehabilitation.…”
Section: Differential Evolution (De)mentioning
confidence: 99%
See 1 more Smart Citation
“…• Zakaryan et al [58] used a weight-sum-based DE [59] to retrieve the optimal link and joint weights that minimize (i) the total mass of the device, (ii) the maximal magnitudes of cable tensions, and (iii) the maximal difference between magnitudes of agonist-antagonist cable tensions (i.e., to resemble the structure of the natural muscular system of human limbs) of their arm exoskeleton for rehabilitation.…”
Section: Differential Evolution (De)mentioning
confidence: 99%
“…There are a few exceptions featuring more than two objectives, and we observed some issues regarding how they were implemented or reported. McDaid [65] and Zakaryan et al [58] solved three-objective problems with weighted-sum-based EAs, which do not require non-dominated sorting but have the drawbacks described in Section 4.1.3. Paez et al [63] solved a four-objective problem with NSGA-II; however, the last one was optimized independently, and the authors did not specify whether a single-objective GA was appositely used for that objective or how it was included in the whole problem without conflicting with the other three.…”
Section: Multi Objectivementioning
confidence: 99%
“…Being fundamentally different from traditional rigid robots, soft robots possess infinite degrees of freedom (DOF) and use materials with nonlinear properties that require innovations in their control systems [13]. Here, biological control methods come to the aid too, which have been used and studied by authors being applied to human upper link exoskeletons [14]. In particular, it is shown that the CPG can control both rhythmic oscillatory and discrete movements [15], which compose the positioning motion of the robot for catching the foreign body and swallowing.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the upper limb as a multi-muscle redundant system, a similar overactuated but cable-driven mechatronic system is developed [34] to imitate upper limb motor functions (Fig. 2.7).…”
Section: Active and Passivementioning
confidence: 99%
“…Fit and comfort are critical to adopting exoskeleton devices, and they are usually evaluated subjectively through questionnaires and surveys. In 2020 [34], [214] begins the process of quantifying the comfort limits of physical interactions on the human body Recent literature emphasises the importance of comfort in the design of exosuits and other assistive devices that physically augment humans; however, there is little quantitative data to aid designers in determining what level of force makes users uncomfortable.…”
Section: Shoulder Comfort Limitsmentioning
confidence: 99%